Synthesis and characterization of mixed-ligand copper(II) saccharinate complexes containing tridentate NNS Schiff bases. X-ray crystallographic analysis of the free ligands and one complex - Omar, Siti Aminah; S. A. Ravoof, Thahira Begum; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne (Springer, 2014)
Four new Schiff bases containing N and S heteroatoms (HL1–HL4) have been prepared and characterized, including determination of the X-ray crystal structures of HL1 and HL3. Spectroscopic evidence indicates that these Schiff bases behave as uninegatively charged tridentate NNS ligands in complexes of general formula [Cu(Ln)sac] (Ln is the anionic form of NNS, and sac represents saccharinate anion). Crystals of both HL1 and [Cu(L4)sac)(H2O)]·Hsac crystallized in triclinic system with P 1¯ space group, while HL3 crystallized in monoclinic system with P 21/c space group. [Cu(L4)sac)(H2O)]·Hsac has a distorted square-pyramidal structure with a non-bonded saccharin molecule present in the outer coordination sphere. The tridentate NNS ligands are coordinated to Cu through pyridine nitrogen, azomethine nitrogen and thiolate sulfur atoms, while the fourth and fifth coordination positions are occupied by the N-bonded saccharinate anion and a water ligand, respectively.